Analisis Perbandingan Tingkat Literasi Membaca dan Menyimak Intensif Mahasiswa Semester Awal - Habiburrahman, Lalu; Harisanti, Baiq Muli (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study compared the listening and intensive reading abilities of early semester students, Mandalika University of Education (n=43) through a descriptive phenomenological approach. The research instruments consisted of the video